Ano ang f (x) * g (x) kapag f (x) = 4x-3 at g (x) = 3x + 1?

Ano ang f (x) * g (x) kapag f (x) = 4x-3 at g (x) = 3x + 1?
Anonim

Sagot:

Tingnan ang proseso ng solusyon sa ibaba:

Paliwanag:

#f (x) * g (x) = (kulay (pula) (4x) - kulay (pula) (3)) xx (kulay (asul) (3x)

#f (x) * g (x) = (kulay (pula) (4x) xx kulay (asul) (3x)) + (kulay (pula) (4x) xx kulay (asul) pula) (3) xx kulay (asul) (3x)) - (kulay (pula) (3) xx kulay (asul) (1)) #

#f (x) * g (x) = 12x ^ 2 + 4x - 9x - 3 #

#f (x) * g (x) = 12x ^ 2 + (4 - 9) x - 3 #

#f (x) * g (x) = 12x ^ 2 + (-5) x - 3 #

#f (x) * g (x) = 12x ^ 2 - 5x - 3 #